2019
DOI: 10.1155/2019/4741252
|View full text |Cite
|
Sign up to set email alerts
|

Killing Two Angry Birds with One Stone: Autophagy Activation by Inhibiting Calpains in Neurodegenerative Diseases and Beyond

Abstract: Proteolytic machineries execute vital cellular functions and their disturbances are implicated in diverse medical conditions, including neurodegenerative diseases. Interestingly, calpains, a class of Ca2+-dependent regulatory proteases, can modulate the degradational system of autophagy by cleaving proteins involved in this pathway. Moreover, both machineries are common players in many molecular pathomechanisms and have been targeted individually or together, as a therapeutic strategy in experimental setups. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 172 publications
(200 reference statements)
1
20
0
Order By: Relevance
“…However, damaging calpain overactivation has been detected in other neurodegenerative disorders, such as Alzheimer disease, amyotrophic lateral sclerosis, Parkinson disease, or the group of polyQ disorders 14 . This calpain overactivation can be caused by an increase of intracellular calcium concentration or by a reduction of the natural endogenous inhibitor calpastatin.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, damaging calpain overactivation has been detected in other neurodegenerative disorders, such as Alzheimer disease, amyotrophic lateral sclerosis, Parkinson disease, or the group of polyQ disorders 14 . This calpain overactivation can be caused by an increase of intracellular calcium concentration or by a reduction of the natural endogenous inhibitor calpastatin.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, enhanced calpain activation can contribute to the compromised activation of this degradation pathway. Various studies have found that the impact of calpains on autophagy occurs on multiple levels, such as reduction of autophagy initiation or switching from autophagy to apoptosis 14 . Several neurodegenerative disorders exhibit an overactivation of calpains and disturbances of the autophagic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations